HEAVY METALS AND TOXIC TRACE ELEMENTS CONTENTS IN SOILS OF SELECTED AREAS OF THE KAVALA PREFECTURE, NORTHERN GREECE - Papastergios, G.; Georgakopoulos, A.; Femândez-Turiel, J. L.; Gimeno, D.; Filippidis, A.; Kassoli-Fournaraki, A.; Grigoriadou, A. (Bulletin of the Geological Society of Greece, 2004)
In the present study a total of sixteen samples (3 surrounding rocks and 13 uncultivated topsoils) from the industrial zone east of the city of Kavala, Northern Greece, was collected and analyzed for their content in 41 elements. The extraction of the elements was based on the digestion of 0.1 g of each sample with 2 ml HNO3 and the soil fraction used was the < 20Όμιη. The analytical methods used were ICP-OES for the elements Ca, Mg, Κ, Β, Sr, Fe, Na, Si, S, Ρ, and ΑΙ and ICPMS for the elements Mn, Zn, Cu, Ti, V, Cr, Rb, Ba, Th, La, Ce, As, Sn, Co, Se, Y, Zr, Mo, Cd, Cs, W, Sb, Li, U, Ag, Ni, Hg, Ga, Ge and Pb. The mean element concentrations of the thirteen topsoil samples were compared with the mean values for soil types Fluvisols and Leptosols. The results showed that they are enriched for the elements Ag, As and Pb by 21, 15 and 3 times, respectively. Moreover, the topsoils were compared with the three surrounding rock samples. The results showed that the concentrations of Ca, Mg, Κ, Fe, Si, S, AI, Ρ Na, Β, Ce, Co, Cs, Ga, Ge, Hg, La, Li, Mo, Ni, Rb, Se, Sn, Sr, Th, U and W in the topsoils are mainly influenced by their concentrations in the surrounding rocks. The elements Ag, As, Ba, Cd, Cr, Cu, Mn, Pb, Sb, Ti, Y, V, Zn, and Zr are enriched in the topsoils. The enrichment of Ag, As, Cd, Cr, Cu, Mn, Pb, Sb, and Zn is mainly due to the widespread presence of PBG sulphides, Mn, Cd, and As in the surrounding mineralizations. The enrichment took place, quite possibly, during the formation of Drama and Nestos basins, during Tertiary, and is possibly being continued until today. However, the human activities that take place in the area are also, at least partially, responsible for this enrichment.